PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA PERUSAHAAN HOTEL MELIA BALI - Warniti, Ni Putu Putri; Purnawati, Ni Ketut; Setiawan, Putu Yudi; Dana, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024, 2024)
Company Company performance is a measuring tool to determine the company's ability to operate in creating competitive advantage and achieving the goals set by the company. This study aims to explain the effect of total quality management on company performance. This research was conducted at the Melia Bali Hotel with a total population of 239 people, and the number of samples taken was 150 respondents. The data analysis technique used is multiple linear regression analysis. The results show that customer focus, teamwork, continuous system improvement, and education and training have a positive and significant effect on company performance. Preferably, the Melia Bali Hotel, in order to improve cooperation between employees to create harmonious relationships, provide regular education and training to employees to improve the skills and expertise needed by the company so that the company's performance can increase.